Media Internet Sarana Meningkatkan Proses Belajar Anak-Anak - Reza Yori Pahlevi; Randa Putra Sinaga (Yayasan Literasi Sains Indonesia, 2022)
The world of education today is influenced by progress of technology and internet. One of the technologies and the internet that engage in education is online learning. Online learning as an intermediary between educators and students with a supportive internet network, a wide range of media used as online learning as research subjects, for example: WhatsApp, Zoom Meet, Google Classroom, YouTube. The purpose of this study was to analyze the effectiveness in the use of technology and the internet as a medium for learning. The method used in this article is to collect question and answer data to the informants, namely students through interviews. The results of the study concluded that overcoming learning difficulties did require the use of technology and the internet as learning media.